Synthesis and ligand substitution reactions of κ4-B, S, S′, S′′-ruthenaboratranes. Issue 1 (5th December 2018) - Foreman, Mark R. St.-J.; Hill, Anthony F.; Ma, Chenxi; Tshabang, Never; White, Andrew J. P.
Abstract : Ruthenaboratranes of the form [Ru(CO)Lκ 4 -B(mt)3 ] (mt = N -methimazolyl) arise via substitution of the PPh3 ligand in [Ru(CO)(PPh3 )κ 4 -B(mt)3 ] by L (L = PMe2 Ph, PMe3, P(OMe)3, P(OEt)3, P(OPh)3 ) or reactions of [RuCl(R)(CO)L n ] (R = Ph, CH{CHPh; n = 2, L = PCy3 ; n = 3, L = P(OMe)3, PMe2 Ph) with Na[HB(mt)3 ]. Abstract : A range of ruthenaboratranes of the form [Ru(CO)Lκ 4 - B, S, S ′, S ′′-B(mt)3 ] (mt = N -methylmercaptoimidazolyl) have been prepared either by substitution of the PPh3 ligand in [Ru(CO)(PPh3 )κ 4 - B, S, S ′, S ′′-B(mt)3 ] by L (L = PMe2 Ph, PMe3, P(OMe)3, P(OEt)3, P(OPh)3 ) or reactions of [RuCl(R)(CO)L n ] (R = Ph, CH{CHPh; n = 2, L = PCy3 ; n = 3, L = P(OMe)3, PMe2 Ph) with Na[HB(mt)3 ].